Instructional Technology: Teacher’s Initial Perception of TPACK in Physics Learning - Depi Oktasari; Disa Hediansah; Jumadi Jumadi; Warsono Warsono (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
The demands of learning in the industrial era 4.0 currently have an impact on innovative learning, learning design with the Technology Pedagogic and Content Knowledge (TPACK) framework provides a useful framework for teachers and researchers to integrate technology in learning activities. The TPACK (Technological Pedagogic Content Knowledge) framework is the latest issue that is relevant to 21st Century learning concepts. This study aims to examine the extent of teacher responses in utilizing learning information sources using TPACK priority scales in encouraging student learning abilities. This study used a quasi-experimental study analytic test of the randomized design with questioner testing. The concept of the approach is through two methods, namely, qualitative and quantitative approaches. The research subjects were carried out randomly with a target sample of physics teachers in the category of new instructors from several provinces in Indonesia, with 33 active respondents in their fields. Based on the results of the study, TPACK is an essential point to give the powerful managing of educational learning and field studies show that the teacher states that some obstacles are experienced when integrating technology in learning physics at school to make sure instructional technology.